Platinum-Functionalized Hierarchically Structured Flower-like Nickel Ferrite Sheets for High-Performance Acetone Sensing - Ziwen Yang; Zhen Sun; Yuhao Su; Caixuan Sun; Peishuo Wang; Shaobin Yang; Xueli Yang; Guofeng Pan (Chemosensors)
Acetone detection is crucial for non-invasive health monitoring and environmental safety, so there is an urgent demand to develop high-performance gas sensors. Here, platinum (Pt)-functionalized layered flower-like nickel ferrite (NiFe2O4) sheets were efficiently fabricated via facile hydrothermal synthesis and wet chemical reduction processes. When the Ni/Fe molar ratio is 1:1, the sensing material forms a Ni/NiO/NiFe2O4 composite, with performance further optimized by tuning Pt loading. At 1.5% Pt mass fraction, the sensor shows a high acetone response (Rg/Ra = 58.33 at 100 ppm), a 100 ppb detection limit, fast response/recovery times (7/245 s at 100 ppm), and excellent selectivity. The enhancement in performance originates from the synergistic effect of the structure and Pt loading: the layered flower-like morphology facilitates gas diffusion and charge transport, while Pt nanoparticles serve as active sites to lower the activation energy of acetone redox reactions. This work presents a novel strategy for designing high-performance volatile organic compound (VOC) sensors by combining hierarchical nanostructured transition metal ferrites with noble metal modifications.